Involvement of endoplasmic reticulum stress in rifampicin-induced liver injury - Hou, Wanqing; Nsengimana, Bernard; Yan, Chuyun; Nashan, Bjorn; Han, Shuxin (Frontiers in Pharmacology, 2022)
Rifampicin is a first-line antituberculosis drug. Hepatocyte toxicity caused by rifampicin is a significant clinical problem. However, the specific mechanism by which rifampicin causes liver injury is still poorly understood. Endoplasmic reticulum (ER) stress can have both protective and proapoptotic effects on an organism, depending on the environmental state of the organism. While causing cholestasis and oxidative stress in the liver, rifampicin also activates ER stress in different ways, including bile acid accumulation and cytochrome p450 (CYP) enzyme-induced toxic drug metabolites via pregnane X receptor (PXR). The short-term stress response helps the organism resist toxicity, but when persisting, the response aggravates liver damage. Therefore, ER stress may be closely related to the "adaptive" mechanism and the apoptotic toxicity of rifampicin. This article reviews the functional characteristics of ER stress and its potentially pathogenic role in liver injury caused by rifampicin.